Intangible aspect of revitalization in vernacular heritage architecture in case study of Wae Rebo NTT Village - Afifah, N; Kurniawan, K R (ASCEE, 2022)
Revitalization is an effort to preserve traditional architecture. The form of revitalization in traditional architecture has certain values and principles, which can be seen from both tangible and intangible aspects. These two aspects have different responses in the revitalization process. In the tangible aspect, we can measure the impact through a quantitative approach, while in the intangible aspect, we can measure it using a qualitative approach. This paper answers the question of how the intangible aspects of revitalization impact the sustainability of traditional architectural values. It carries the research method of using qualitative methods and theoretical studies, and comparing those aspects of the revitalization process. The results are explained by defining the positive and negative effects on the last condition of revitalization.